2020
DOI: 10.1177/0266666920939601
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and socio-economic differences in financial information literacy among university students

Abstract: Financial information literacy helps to manage earnings, especially among those students who study non-commerce subjects. Thus, this study attempts to explore the differences in such literacy through their demographic and socioeconomic characteristics. A well-structured instrument was used to gather data from 382 non-commerce students in universities in Pakistan using a multi stage sampling technique. Analyses were conducted through percentage of correct response technique and group comparisons. The findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 41 publications
3
25
0
5
Order By: Relevance
“…The finding about IL is in line with that of Mahmood (2013), Ode (2017) who reported that gender had no apparent influence on IL skills. However, some studies found association between gender and IL skills and reported that females appeared to be more discerning than males in IL skills (Naveed and Rafique, 2018; Punter et al , 2017; Taylor and Dalal, 2017) while others found males ahead of females in this regards (Baro and Fyneman, 2009; Liaqat, Mahmood and Ali, 2021; Liu and Sun, 2012; Tella and Mutula, 2008). Similar trend regarding PIM practices and gender relationship was noted in literature.…”
Section: Discussionmentioning
confidence: 99%
“…The finding about IL is in line with that of Mahmood (2013), Ode (2017) who reported that gender had no apparent influence on IL skills. However, some studies found association between gender and IL skills and reported that females appeared to be more discerning than males in IL skills (Naveed and Rafique, 2018; Punter et al , 2017; Taylor and Dalal, 2017) while others found males ahead of females in this regards (Baro and Fyneman, 2009; Liaqat, Mahmood and Ali, 2021; Liu and Sun, 2012; Tella and Mutula, 2008). Similar trend regarding PIM practices and gender relationship was noted in literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more attention has been focused on the development of information literacy in various, diverse and specific fields in recent years. Liaqat et al ( 2020 ) proved that financial information literacy can help manage earnings, Ahmad et al ( 2020 ) investigated the relationship between CEO information literacy and innovation in enterprises, and Chebet and Cheruiyot ( 2020 ) identified the contributions of farmers’ information literacy to productivity and profitability. The topic is of great significance to improve citizens' lives and work, promote social progress and eliminate the information gap.…”
Section: Discussionmentioning
confidence: 99%
“…Liaqat at al. [3] investigated attempted to examine differences in such literacy through their demographic and socioeconomic characteristics, level of financial knowledge among university students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial information literacy helps to manage earnings, especially among those students who study non-commerce subjects Liaqat at al. [3]. In this regard, the improvements in the financial literacy of the individuals through various education programs will probably raise the demand of financial products with different risk characteristics and in turn contribute to the development of financial sector Bayar at al.…”
Section: Introductionmentioning
confidence: 99%